Media and Communication in Age of Bliss and Previous Periods - Erbil, Kadir (Fırat University, 2022)
Media; It is a concept that encompasses all mass media. The most important task; the principle of impartiality and meeting the needs of the public for freedom of information. The media has facilitated the awareness, education, orientation and dissemination of all kinds of information in all fields. Today's media affects people's needs and desires positively or negatively. Media is like a double-edged sword. It has both positive and negative aspects. Human beings needed to know and understand each other after they settled down. For this reason, people have tried to communicate with each other in various ways. As time passed, the means of communication used in society developed and written communication was changed from verbal communication. Before Islam, Arabs were in contact with the societies living around them. Arab tribes communicated among themselves through various means such as poetry, eulogy, oratory, setting mountain tops on fire, and homing pigeons. Since Arabia has been on two important trade routes for a long time, they made international communication through trade. The most important methods applied for communication in the period of ignorance; poetry, ode, oratory, club, fair etc. they used to eat. The Prophet started his first invitation by communicating with people in the first years of his prophethood. He held personal meetings with various tribesmen who came to Mecca during certain seasons. During the Meccan period, With the first revelation to the Prophet, he began to invite all humanity to Islam in the person of the Meccan society. The Prophet tried to convey his messages to the Meccan society by specifying the characteristics and purposes of his invitation. The notables of the Makkan polytheists did not take him seriously, The notables of the Makkan polytheists did not take him seriously, they mocked him and described him as a magician, poet, soothsayer, magician, separator, madman and demonized. Despite all these slanders, The Prophet continued to announce his message by communicating with everyone at all times and places. After the Prophet's migration from Mecca to Medina, communication and communication areas with the people in Medina became easier. The Prophet communicated with the kings and rulers of neighboring countries by sending letters to invite them to Islam. She also sent a letter to the Jews living in Medina, inviting them to abide by the agreements and promises they made. He strengthened communication with the Arab delegations who came to Medina to become Muslims and the delegations sent to meet with the Arab tribes. The Prophet communicated with the polytheists during the peace process with the Treaty of Hudaybiyah. On the one hand, the Tabuk Campaign to the Byzantine border to secure the borders of the Muslims in Medina became a means of communication for both the border and surrounding tribes. The Prophet's explanation, interpretation and hadiths of the Qur'an from the beginning of his prophethood have been the greatest media power for Muslims. The Prophet used various communication methods in his communication with people. While communicating with them, he took into account the characteristics of people and society. He tried to communicate with people at every opportunity.

Bugün dünya, haberleri ve olayları anında tüm bireylerin öğrendiği küçük bir köy haline gelmiştir. Bu araştırmanın amacı; orta çağ ve Asr-ı Saadet döneminde nasıl bir medya ve vardı, medya organları nelerdi, Kur’an-ı Kerim’de medya ile ilgili nasıl bir mesaj vardır? gibi soruların cevabını bulmak ve bunları aydınlatmaktır. Medyanın insanın kendisi kadar eski bir sosyal hareket olduğundan hareketle, İslam öncesi medya, bazı eski toplumları ve Araplardaki medyayı tanımak gerekir. Dünya tarihinde meydana gelen olayların hemen hepsinde medya olumlu veya olumsuz önemli rol oynamıştır. Kur’an’da iletişim; yöntemleri, konusu veya çeşitli sanatları bakımından çağdaş medyadan farklı değildir. Ancak özünde, içeriğinde, biçiminde İslam’ın ruhundan türetilen özel bir karaktere sahiptir. İslami medya olgusu, belirli, açık ve bütünleşik bir hedefe ulaşmak ve bu yürüyüşün yönünü belirleyen kurallara göre dürüst haber, eğitim ve öğretimi hedeflemiştir. Böylece çalışmamız aşağıdaki başlıklar altında incelenmiştir; Asr-ı saadet ve önceki dönemlerde medya ve iletişim konusunu Arapların eski medeniyetlerle iletişimi, Arap Yarımadası’ndaki sosyal medya organları ve iletişim, İslam’ın ilk dönemlerinde medya ve iletişim, Hz. Peygamberin peygamberliğinin başında iletişim, Hz. Peygamber ve Mekke döneminde medya ve iletişim, Medine döneminde medya ve iletişim, sahabe döneminde medya ve iletişim, Hz. Peygamber’in (s) gönderdiği mektuplar ve elçiler ve Kur’an-ı Kerim’de iletişim başlıkları altında incelemeye çalıştık.
Asr-ı Saadet ve Önceki Dönemlerde Medya ve İletişim
Keywords: Religious Studies; Din Araştırmaları